2002
DOI: 10.1126/science.1072994
|View full text |Cite|
|
Sign up to set email alerts
|

The Amyloid Hypothesis of Alzheimer's Disease: Progress and Problems on the Road to Therapeutics

Abstract: It has been more than 10 years since it was first proposed that the neurodegeneration in Alzheimer's disease (AD) may be caused by deposition of amyloid beta-peptide (Abeta) in plaques in brain tissue. According to the amyloid hypothesis, accumulation of Abeta in the brain is the primary influence driving AD pathogenesis. The rest of the disease process, including formation of neurofibrillary tangles containing tau protein, is proposed to result from an imbalance between Abeta production and Abeta clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

146
9,573
11
87

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12,395 publications
(9,817 citation statements)
references
References 88 publications
146
9,573
11
87
Order By: Relevance
“…Aggregation and deposition of β‐amyloid (Aβ) and the formation of neurofibrillary tangles are classical hallmarks of AD (Hardy and Selkoe, 2002). Aβ deposition in the brain seems to precede neurofibrillary tangle formation, neuronal cell death and subsequent functional decline (Jack et al, 2010).…”
Section: Astrocytes In the Diseased Brain Are Central To Neuropathologymentioning
confidence: 99%
“…Aggregation and deposition of β‐amyloid (Aβ) and the formation of neurofibrillary tangles are classical hallmarks of AD (Hardy and Selkoe, 2002). Aβ deposition in the brain seems to precede neurofibrillary tangle formation, neuronal cell death and subsequent functional decline (Jack et al, 2010).…”
Section: Astrocytes In the Diseased Brain Are Central To Neuropathologymentioning
confidence: 99%
“…Alzheimer's disease (AD) -the most common form of age-related dementia -is a progressive neurodegenerative disorder characterized by a deficit in cognitive processes that are manifested as alterations in memory, judgment and reasoning (reviewed in Hardy and Selkoe, 2002). To date, several studies have shown that the Wnt signaling components b-catenin and GSK3b form multiprotein complexes with the early-onset familial AD-linked presenilin proteins (Zhou et al, 1997;Takashima et al, 1998b;Kang et al, 2002).…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 99%
“…The accumulation of amyloid‐β (Aβ) plaques in the brain is one of the first events in the pathological cascade leading to Alzheimer's disease (AD) (Bateman et al., 2012; Hardy & Selkoe, 2002; Sperling et al., 2010). Aβ disrupts synaptic functioning, resulting in aberrant brain connectivity at the synaptic level (Selkoe, 2002; Spires‐Jones & Hyman, 2014), as well as on the whole‐brain connectivity level (Delbeuck, der Linden, & Collette, 2003; Hedden et al., 2009).…”
Section: Introductionmentioning
confidence: 99%